A New Minimally Invasive Treatment for Cesarean Scar Pregnancy and Cervical Pregnancy. Issue 1 (January 2017) - Timor-Tritsch, Ilan E.; Monteagudo, Ana; Bennett, Terri-Ann; Foley, Christine; Ramos, Joanne; Kaelin Agten, Andrea
Abstract : (Abstracted from Am J Obstet Gynecol 2016;215:351.e1–351.e8) The occurrence of cesarean scar pregnancy and cervical pregnancy, unrelated forms of pathological pregnancies, present significant diagnostic and treatment challenges. A large number of treatments have been used with widely varying effectiveness and complication rates ranging from 10% to 62%.